2004
DOI: 10.1007/s11882-004-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for food allergy

Abstract: Food allergy is a common problem that often affects young children. Numerous factors affect the development of food allergy both prenatally and postnatally. These factors are genetic and environmental. Although little can be done post-conception to alter a child's genetic risk for developing food allergy, early identification may permit alterations of the environment in which food allergy develops. Environmental factors operate both prenatally and postnatally. By understanding how these factors affect developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…While the risk of food hypersensitivity has both prenatal and postnatal risk factors (Schuller, 2005), at least part of the early life risk appears to be predictable based on immune functional profiles at birth. Prescott et al (2008) found that cord blood monocytes stimulated with TLR‐2, 4, and 5 activators produced more IL‐6 among children who would develop food allergy at 12 months of age compared with those who were non‐allergic in later life.…”
Section: Introductionmentioning
confidence: 99%
“…While the risk of food hypersensitivity has both prenatal and postnatal risk factors (Schuller, 2005), at least part of the early life risk appears to be predictable based on immune functional profiles at birth. Prescott et al (2008) found that cord blood monocytes stimulated with TLR‐2, 4, and 5 activators produced more IL‐6 among children who would develop food allergy at 12 months of age compared with those who were non‐allergic in later life.…”
Section: Introductionmentioning
confidence: 99%